A Capable System for Hiding Image in an Image - Ganesh, R.; Thabasu Kannan, S. (Asian Journal of Engineering and Applied Technology, 2017)
In this paper, we have proposed a new method by for hiding an image using steganographic called GanKan. This method is based on Least Significant Bit (LSB) replacement and can be used for 24 bit color image capable of producing a secret-embedded image. This paper clearly showed that this GanKan new method is better than LSB technique for 8 bit color image and 24 bit color image. Firstly LSB method for both 8 bit and 24 bit color image are described and then the GanKan method for 24 bit color image, compare their result by calculating Peak Signal-to-Noise Ratio (PSNR), Mean Squared Error (MSE), Root Mean Square Error (RMSE) and histogram analysis. LSB Algorithm embedded MSB of secret image into LSB of cover image. In the case of 24 bit color image two methods are described. In first method, last 2 LSB of each plane (RGB) of cover image, is replaced by 2 MSB of secret image. In the second method, last LSB of each red plane is replaced by first MSB of secret image, last 2 LSB of each green plane by next 2 MSB of secret image and then last 3 LSB of blue plane is replaced by next 3 MSB of secret image. This means that total 6 bits of secret image can be hided in 24 bit color image. Experimental results showed that the embedded-image is visually indistinguishable from the original cover-image in the case of 24 bit.